2019
DOI: 10.1080/0284186x.2019.1594363
|View full text |Cite
|
Sign up to set email alerts
|

Patient explicit consideration of tradeoffs in decision making about rectal cancer treatment: benefits for decision process and quality of life

Abstract: Introduction: Patient preferences are often not discussed in treatment decisions in oncology. We introduced an online values clarification method (VCM) to help newly diagnosed rectal cancer patients participate in shared decision making about short-course preoperative radiotherapy. Material and Methods: We offered a link to the VCM to a subset of consecutive patients before the pretreatment consultation with the radiation oncologist. Consultations were audiotaped and coded for expressions of patient preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The study was powered on the primary outcome measure. In a previous (unpublished) study of our group, 49 we found a mean score on this 7-point scale of 5.06 with a standard deviation of 1.70. To be able to detect a difference of 0.5 in an analysis of variance (ANOVA) between-subjects analysis with a power of 80% and an alpha of 5%, 91 participants per experimental condition were needed (i.e., N = 364 participants in total).…”
Section: Methodssupporting
confidence: 57%
“…The study was powered on the primary outcome measure. In a previous (unpublished) study of our group, 49 we found a mean score on this 7-point scale of 5.06 with a standard deviation of 1.70. To be able to detect a difference of 0.5 in an analysis of variance (ANOVA) between-subjects analysis with a power of 80% and an alpha of 5%, 91 participants per experimental condition were needed (i.e., N = 364 participants in total).…”
Section: Methodssupporting
confidence: 57%
“…The presented HRQoL effects of a stoma and major LARS in this study might provide information that can be used as patient information to assist in shared decision-making. Furthermore, explicit patient consideration of the trade-off between anastomosis or a stoma might positively influence the long-term quality of life and lead to a higher acceptance of possible consequences [48].…”
Section: Discussionmentioning
confidence: 99%
“…European studies demonstrate that the proportion of patients with colorectal cancer treated following national guidelines varies between 53 and 90%, with patient preference (27%) and functional status (20%) the most commonly reported reasons for adjusted treatment [ 46 ]. Nonetheless, patient involvement in perceiving personal preferences about the treatment is not systematic, especially in older patients [ 47 ]. Diefenhardt et al showed that in patients with rectal cancer, adherence to neoadjuvant chemo-radiotherapy was significantly associated with disease-free survival [ 44 ].…”
Section: Resultsmentioning
confidence: 99%